Optimal species composition for stand establishment in root-rot infected forest areas - Ahtikoski, Anssi; Honkaniemi, Juha; Holmström, Eero; Peltoniemi, Mikko (Springer Nature, 2024)
Heterobasidion root rot causes severe problems in the coniferous dominated forests of Northern hemisphere by decreasing timber value, reducing tree growth and making trees prone to other disturbance agents such as wind and bark beetles. According to current practices an infected stand is protected by treating fresh stumps at final cutting and generating the stand with tree species other than the host to reduce the current infection levels. However, prevailing guidelines do not provide instructions how to manage the neighbouring stands around the already infected stand. In contrast to earlier studies, we expand the analysis to an entity (a landscape) consisting of both infected and uninfected stands so that stand establishment of uninfected area is taken into account, too. The objective of the study is to optimize stand establishment of the uninfected area so that the revenue losses are simultaneously minimized when the average carbon storage is maximized within the whole landscape (infected + uninfected). Our results demonstrate the complexity of Heterobasidion root rot management: the optimum stand establishment strategy differs depending on the geographic location and interest rate (i.e., yield on capital). Further, the results implicate that for successful fight against Heterobasidion root rot the magnitude of infected area as well as the severity of the infection need to be taken into account.
Keywords: Heterobasidion; root rot; optimisation; forest management; landscape